Efeitos do treinamento dos músculos do assoalho pélvico individual versus individual com progressão para grupo versus em grupo para mulheres com incontinência urinária de esforço: ensaio clínico randomizado - Figueiredo, Vilena Barros de (Universidade Federal de São Carlos, 2018)
The International Continence Society has defined urinary incontinence (UI) as any involuntary loss of urine, which can be classified into several types, most commonly reported in the literature are stress urinary incontinence, urge incontinence and mixed incontinence (association between stress symptoms and urgency). Pelvic floor muscle training (TMAP) is recommended as the first conservative treatment option for urinary incontinence in women and can be practiced individually or in a group. This thesis was composed by two studies. Study I aimed to: Evaluate the effects of individual physical therapy versus individual treatment with group progression versus group-only training in women with stress urinary incontinence. This was a randomized clinical trial. Ninety women over 18 years of age and with complaints of stress urinary incontinence (including those who had complaints of mixed urinary incontinence) were included. The mean age of study participants was 53 ± 12.5 years. After the intervention, the severity measurement improved in all three groups (p <0.001). The benefits of TMAP were maintained 3 and 6 months after completion of supervised training. The groups whose individual and individual training with progression to the group had a significant improvement in pelvic floor muscle function when compared to that trained only in the group after 12 training sessions (p <0.001). Study II aimed to evaluate the responsiveness of Pelvic Floor Distress Inventory-20 (PFDI-20) and Pelvic Floor Impact Questionnaire-7 (PFIQ-7) questionnaires. These questionnaires were designed to evaluate the occurrence of pelvic floor dysfunctions and how much these dysfunctions affect the quality of life. This was a prospective observational study with 72 women with urinary incontinence. The participants answered the questionnaires PFDI-20 and PFIQ-7 before and after the TMAP. Seventy-two women (mean age 51.8 ± 11.9) with stress urinary incontinence (n = 33) and mixed urinary incontinence (n = 39) were recruited. PFDI-20 and PFIQ-7 Portuguese version (Brazil) presented moderate responsiveness after TMAP and can be safely used by physiotherapists to use them in their practices.
Effects of individual pelvic floor muscle training versus individual treatment with progression to group versus group training for women with stress urinary incontinence: randomized controlled trial
Keywords: Fisioterapia; Incontinência urinária de esforço; Qualidade de vida; Músculos do assoalho pélvico; Physiotherapy; Urinary incontinence stress; Quality of life; Pelvic floor muscle; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL